Metastatic urinary bladder paraganglioma on Ga-68 DOTATATE PET/CT - Ko, Andrew (Radiol Case Rep, 2021)
Paragangliomas are extra-adrenal catecholamine-secreting neuroendocrine tumors that can present with adrenergic signs and symptoms. The urinary bladder is a rare location for a paraganglioma, and these tumors must be distinguished from other more common bladder neoplasms. In this case report, we discuss a 59 year-old woman who initially presented with tachycardia, palpitations, chest tightness, shortness of breath, and weight loss. Laboratory evaluation showed significantly elevated catecholamines in the plasma and urine. A CT (Computed Tomography) scan of the abdomen and pelvis revealed an enhancing mass arising from the urinary bladder and an enlarged right pelvic lymph node. A follow up Ga-68 DOTATATE PET/CT (Positron Emission Tomography and/or Computed Tomography) showed increased uptake in the primary bladder mass, right pelvic lymph node, numerous skeletal lesions, and pulmonary nodules, consistent with metastatic paraganglioma of the urinary bladder. This case report demonstrates the radiological findings of metastatic urinary bladder paraganglioma and highlights the importance of skull base to mid-thigh PET/CT using Ga-68 DOTATATE. It is crucial for the radiologist to be familiar with the characteristics of urinary bladder paragangliomas and identify these tumors on imaging to allow prompt initiation of surgical resection and/or systemic therapy.